The Accreditation of Human Resources and Physical Space of the Iranian Heart Centre: Comparison to the national and international standards - Azar Jafari; Masoumeh Bagheri-Nesami; Mohammad Sadegh Rezai; Fatemeh Zamani; Amir Hossein Goudarzian (ACHSM, 2019)
Objective: Standardization of hospital resources and physical space can be an important strategy to increase productivity and effectiveness of services. The study was conducted with the aim of comparative accreditation of human resources and physical space in Mazandaran heart centre compared with the standards. Method: This comparative descriptive study was carried out in Sari city (centre of Mazandaran province) during 2016-2017. The data collection tool consists of two checklists for investigating the physical space and human resources of the hospital. To evaluate the quality of the content, a checklist was distributed to 5 experts from Mazandaran University of Medical Sciences. After corrections the checklist was applied. Data were analyzed by SPSS software version 16 and descriptive statistics. Findings: The total number of nurses in this hospital was 288 and the total number of beds was 171. The human resources in the nursing, nutrition, operating room, anaesthesia departments were not standard. The ratio of total human resource to the number of beds was also estimated as 4.04. Results showed that the physical conditions in the hospital were moderately standard. The physical conditions of the hospital in most dimensions based on checklist, except the physical location of hospital and the features of its doors, were in accordance with the standard requirements. Conclusion: Considering the inappropriate distribution of human resource in the hospital and the non-standard design of physical space for providing services with better quality and increasing patients' satisfaction, it is recommended that experts control more carefully standard requirements.